Adrenaline can restart the heart, but is no good for the brain. (4th March 2019) - Cook, Rob; Davidson, Peter; Martin, Rosie
The study: A randomised trial of epinephrine in out-of-hospital cardiac arrest Perkins GD, Ji C, Deakin CD, Quinn T, Nolan JP, Scomparin C, Regan S, Long J, Slowther A, Pocock H, Black JJM, Moore F, Fothergill RT, Rees N, O'Shea L, Docherty M, Gunson I, Han K, Charlton K, Finn J, Petrou S, Stallard N, Gates S, Lall R for the PARAMEDIC2 Collaborators Published on 18 July 2018 N Engl J Med 2018;379:711-21. This project was funded by the National Institute for Health Research HTA Programme (project number 12/127/126). To read the full NIHR Signal, go to: https://discover.dc.nihr.ac.uk/content/signal-000639/adrenaline-can-restart-the-heart-but-is-no-good-for-the-brain